2019
DOI: 10.5585/iji.v7i1.271
|View full text |Cite
|
Sign up to set email alerts
|

How Technology Intelligence is Applied In Different Contexts?

Abstract: Technology Intelligence is one of the many ways of applying Competitive Intelligence. As CI, TI intends to detect and process weak signals in order to identify opportunities and threats and provide actionable information. There is still a gap in reported cases of companies actually applying Technology Intelligence. This article intends to answer the research question: How companies build an actionable technology intelligence project? Case Study and Action-research approaches were applied for this research. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[28] continue to say that these processes add knowledge to the already existing ones and this in turn enhances the capabilities of firms and gives a clear scenario of the present and future nature of competition programs for executives so that they can be able to make decisions faster and earlier in order to foster growth and expansion for their businesses. [31] in their study found Technological Intelligence to be those actions that assist in decision-making in regard to technology and management in general by utilizing relevant knowledge on technological threats and opportunities as well as facts of the organization's surroundings by gathering, interpreting, and distributing of information.…”
Section: Technological Intelligence Activities and Performancementioning
confidence: 99%
“…[28] continue to say that these processes add knowledge to the already existing ones and this in turn enhances the capabilities of firms and gives a clear scenario of the present and future nature of competition programs for executives so that they can be able to make decisions faster and earlier in order to foster growth and expansion for their businesses. [31] in their study found Technological Intelligence to be those actions that assist in decision-making in regard to technology and management in general by utilizing relevant knowledge on technological threats and opportunities as well as facts of the organization's surroundings by gathering, interpreting, and distributing of information.…”
Section: Technological Intelligence Activities and Performancementioning
confidence: 99%